The Non-Covalent Interactions and In Vitro Radical Scavenging Activities of the Caseinate-Galangin and Caseinate-Genistein Complexes - Chun-Min Ma; Xin-Huai Zhao (MDPI AG, 2019)
Non-covalent interactions and in vitro radical scavenging activities of the complexes formed by the commercial milk protein product caseinate and one of the two polyphenols (galangin and genistein) were assessed by the multi-spectroscopic techniques, molecular docking, and detection of scavenging activities against the 1,1−diphenyl-2-picryl-hydrazyl (DPPH), 2,2′-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), and hydroxyl radicals. The caseinate bound with the two polyphenols showed conformational changes and increased scavenging activities, compared with original caseinate. The caseinate-polyphenol binding was driven by the hydrophobic interaction and hydrogen-bonds, while hydrophobic interaction was the main binding force. Meanwhile, sodium dodecyl sulfate and urea could damage the essential hydrophobic interaction and hydrogen-bonds, respectively, and thus led to decreased apparent binding constants for the caseinate-polyphenol binding. Based on the measured values of several apparent thermodynamic parameters like ΔH, ΔS, ΔG, and donor−acceptor distance as well as the detected radical scavenging activity, galangin having more planar stereochemical structure and random B-ring rotation always had higher affinity for caseinate than genistein having location isomerism and twisted stereochemical structure, while the caseinate-galangin complex showed higher radical scavenging activity than the caseinate-genistein complex. It is thus concluded that both chemical and stereochemical structures of polyphenols are crucial to the affinity of polyphenols for protein and antioxidant activities of the protein-polyphenol complexes.